Potensi Tanaman Sukun (Artocarpus altilis) sebagai Agen Antiinflamasi dan Antidiabetes - Ni Gusti Ayu Diantari; Debby Yunita; Maria Aurelia Afila Tutonugi; Theresia Helena Tokan; Teresia Kiki Oktavianti; Florentinus Dika Octa Riswanto; Dewi Setyaningsih (PT Dexa Medica, 2023)
Background: Artocarpus altilis is a plant whose every part is beneficial for health. In Indonesia, the distribution of this plant is only found in certain places and has not been cultivated. Breadfruit is basically rich in flavonoid, tannin, and saponin compounds that are known to be potential as antidiabetic and antiinflammatory. Diabetes is a group of metabolic disease characterized by hyperglycemia, due to lack of insulin production and/or sensitivity. Type 2 diabetes is a degenerative disease that is a global health problem. Type 2 diabetes is treated using antidiabetic agents and/or insulin. Inflammation is a local reaction of the body characterized by certain symptoms. Treatment of inflammation using synthetic drugs is associated with various side effects. Objective: This review is aimed to provide information about antidiabetic and anti-inflammatory activities in breadfruit plant. Results: Substance of breadfruit plant with antidiabetic efficacy was found in the stem, leaf, and fruit, showed by results of phytochemical test. Antidiabetic activity was proven by in vivo, in vitro, and AlCl calorimetry tests, while anti-inflammatory substance was found in the leaf and fruit, and the anti-inflammatory activity was showed by results of in vivo and in vitro tests. Conclusion: Breadfruit plants can be potentially developed as an alternative treatment for diabetes and inflammation.